Криминальная бригада: [повесть] / Валерий Гусев ; [художник Светлана Киселева] - Гусев Валерий Борисович (Дети Шерлока Холмса, 2008)
Экземпляры: (20220316) / Инвентарный номер: 3601 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Г 96 / ББК: 84(2Рос=Рус)6